Time-varying expected returns : evidence from the united states and the United Kingdom - Sousa, Ricardo M. (2012)
I assess the relative performance of several exmpirical proxies developed in the literature of asset pricing to capture time variation in expected future returns using data for the United States and the United Kingdom. I show that the wealth composition risk by Sousa (2010a) exhibits strong forecasting power and tracks risk premium better than many economically motivated variables.